Skill Variety, Innovation and New Business Formation - Jolanda Hessels; Udo Brixy; Wim Naudé; Thomas Gries (Tinbergen Institute, 2014)
We extend Lazears theory of skills variety and entrepreneurship in three directions. First, we provide a theoretical framework linking new business creation with an entrepreneurs skill variety. Second, in this model we allow for both generalists and specialists to possess skill variety. Third, we test our model empirically using data from Germany and the Netherlands. Individuals with more varied work experience seems indeed more likely to successfully start up a new business and being a generalist does not seem to be important in this regard. Finally, we find that innovation positively moderates the relationship between having varied experiences, and being successful in starting up a new business. Our conclusion is that entrepreneurs with more varied work experience are more likely to introduce innovations that have not only technical, but also commercial value. Our findings support the notion that entrepreneurship can be learned.
Keywords: L26; M13; J24; O31; 330; entrepreneurship; start-ups; human capital; innovation; skills